Marketing Management and Consumer Behavior Perspective on Customer Satisfaction: The Role of Service Quality and Brand Image in Modern Retail - Purba, Mery Lani; Hutagalung, Yuni Lestina; Tambunan, Elisabet; Purba, Roberto Roy (Yayasan Vifada Cendikia Indonesia, 2025)
This study examines the determinants of customer satisfaction in modern retail by analyzing the roles of service quality and brand image within a competitive Indonesian context. The research aims to evaluate the partial and simultaneous effects of these variables on customer satisfaction while highlighting their complementary contributions. A quantitative explanatory approach was employed using a cross-sectional survey of 100 customers at a modern retail outlet in Medan. Data were collected through structured questionnaires and analyzed using multiple linear regression with visit frequency as a control variable. The findings reveal that service quality and brand image both have positive and statistically significant effects on customer satisfaction, with brand image demonstrating a relatively stronger influence. Simultaneously, both variables explain a substantial proportion of variance, indicating that customer satisfaction is shaped by the integration of functional service performance and symbolic brand perceptions. This study implies that retail firms must adopt integrated strategies that enhance service delivery while strengthening brand credibility and emotional engagement. The novelty lies in combining service quality and brand image within a single empirical model at the retail outlet level while incorporating behavioral control variables, offering a more holistic and context-specific understanding of customer satisfaction in modern retail environments today.